Pancreatic neuroendocrine tumors: a review. (March 2015) - Young, Kate; Iyer, Ridhima; Morganstein, Daniel; Chau, Ian; Cunningham, David; Starling, Naureen
ABSTRACT : Neuroendocrine tumors (NETs) are a rare and heterogeneous group of tumors with widely varying morphologies and behaviors. Due to their rarity and heterogeneity, progress in improving their treatment has been slow. However, in recent years there have been advances both in their characterization and in the available treatment options. This review will attempt to address these, with particular reference to pancreatic NETs. Pancreatic NETs are a subset of NETs, previously known as islet cell tumors, which appear to be a distinct biological entity, responding differently to systemic treatments compared with NETs arising elsewhere in the GI tract.